Tracking Economic Value of Products in Natural Settings: A Wireless EEG Study - Roberts, Hannah; Soto, Vicente; Tyson-Carr, John; Kokmotou, Katerina; Cook, Stephanie; Fallon, Nicholas; Giesbrecht, Timo; Stancak, Andrej (Frontiers in Neuroscience, 2018)
Economic decision making refers to the process of individuals translating their preference into subjective value. Little is known about the neural processes that underpin this form of value-based decision making and no studies have investigated these processes outside of controlled laboratory settings. The current study investigated the spatio-temporal dynamics that accompany economic valuation of products using mobile electroencephalography (EEG) and eye tracking techniques. Participants viewed and rated images of household products in a gallery setting while EEG and eye tracking data were collected wirelessly. A Becker-DeGroot-Marschak (BDM) auction task was subsequently used to quantify the individual’s willingness to pay (WTP) for each product. WTP was used to classify products into low, low medium, high medium and high economic value conditions. Eye movement Related Potentials (EMRP) were examined, and Independent Component Analysis (ICA) was used to separate sources of activity from grand averaged EEG data. Four Independent Components (ICs) of EMRPs were modulated by WTP (i.e., subjective value) in the latency range of 150˗250 ms. Of the four value-sensitive ICs, one IC displayed enhanced amplitude for all value conditions excluding low value, and another IC presented enhanced amplitude for low value products only. The remaining two value-sensitive ICs resolved inter-mediate levels of subjective values. Our study quantified, for the first time, the neural processes involved in economic value based decisions in a natural setting. Results suggest that multiple spatio-temporal brain activation patterns mediate the valuation of products. The EMRP parietal P200 component may reflect an attention allocation mechanism that separates the lowest-value products (IC7) from products of all other value (IC4), suggesting that low-value items are categorized early on as being aversive. While none of the ICs showed linear amplitude changes that parallel subjective values of products, results suggest that a combination of multiple components may sub-serve a fine-grained resolution of subjective value of products.